Measuring the effects of mind wandering in people with insomnia: A driving simulator study - Xu, Lin; Yan, Yingying; Dong, Hongming; Qiao, Dandan; Liu, Yanyan; Tian, Junfang; Ai, Zhu; Xue, Rong (Frontiers in Neuroscience, 2022)
Purpose: Studies have shown that people with insomnia experience more frequent and longer episodes of mind wandering (MW) while driving. However, the effect of the interaction between insomnia and MW on driving behavior is not fully understood. This study aimed to gain deeper insights into the relationships among insomnia, MW, and driving behavior. Patients and methods: Forty-two participants (21 diagnosed with insomnia and 21 controls) were recruited, and subjective sleep quality and cognitive function were assessed. A driving simulator experiment with a within-subject design was performed, involving two distraction tasks (no-distraction task versus MW task) and two driving scenarios (lane-keeping versus lane-changing). Results: In the lane-keeping scenario, there was no significant between-group difference (people with insomnia and controls) in longitudinal driving performance for the no-distraction task, although the interaction between MW and insomnia significantly increased drivers’ longitudinal control variation. Correlation analysis confirmed that longitudinal driving performance was positively correlated with sleep quality and the cognitive level. Unlike longitudinal driving performance, lateral driving performance was significantly weaker in people with insomnia than in controls under both distraction tasks. In the lane-changing scenario, although there was no between-group difference in driving performance, the MW task led to significant changes in driving performance within each group compared with the no-distraction task, and these findings were associated with cognitive function, but not sleep quality. Conclusion: These findings show that insomnia and MW combined can lead to reduced driving performance. Further research is needed to elucidate the factors that influence this phenomenon.